2006
DOI: 10.1210/jc.2005-2460
|View full text |Cite
|
Sign up to set email alerts
|

Urine Steroid Hormone Profile Analysis in Cytochrome P450 Oxidoreductase Deficiency: Implication for the Backdoor Pathway to Dihydrotestosterone

Abstract: The increased androsterone excretion during early infancy, as compared with the etiocholanolone and 11-hydroxyandrosterone excretions in the same period, suggests the presence of the backdoor pathway in PORD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 16 publications
4
117
0
Order By: Relevance
“…Four POR variants that the authors found in the BioVentures Web data base (P228L, R316W, G413S, and G504R) were also analyzed. Most recently, Homma et al (10) described the POR mutations Q201X, A462_S463insIA, and E580Q.…”
Section: Antley-bixler Syndrome (Abs)mentioning
confidence: 99%
“…Four POR variants that the authors found in the BioVentures Web data base (P228L, R316W, G413S, and G504R) were also analyzed. Most recently, Homma et al (10) described the POR mutations Q201X, A462_S463insIA, and E580Q.…”
Section: Antley-bixler Syndrome (Abs)mentioning
confidence: 99%
“…Serum concentrations of AAS are of particular importance and often monitored for diagnosis, treatment or research on the relationship between their concentrations and diseases [8][9][10][11]. Urinary concentrations are also received great attention because of its noninvasive detection [12][13][14]. Furthermore, AAS are even misused by athletes to improve their sports performance [6,15].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, androgen metabolites showed a clear overlap that can be explained by androgen production in the backdoor pathway (Fig. 1, dashed arrow), which is proven in the tammar wallaby (12 ) and postulated in the human newborn (13 ). Androsterone can be derived not only from AD4 and dihydrotestosterone in the conventional pathway but also from 5␣-pregnane-3␣,17␣-diol-20-one in the backdoor pathway (12,13 ).…”
Section: Biochemical Diagnosis Of C21ohd and Pordmentioning
confidence: 85%
“…Androsterone can be derived not only from AD4 and dihydrotestosterone in the conventional pathway but also from 5␣-pregnane-3␣,17␣-diol-20-one in the backdoor pathway (12,13 ). In PORD, androsterone could increase during early infancy (13 ), resulting in overlap in androgen metabolites.…”
Section: Biochemical Diagnosis Of C21ohd and Pordmentioning
confidence: 99%